0.5 V, Low-Power Bulk-Driven Current Differencing Transconductance Amplifier - Montree Kumngern; Fabian Khateb; Tomasz Kulej (Sensors)
This paper presents a novel low-power low-voltage current differencing transconductance amplifier (CDTA). To achieve a low-voltage low-power CDTA, the BD-MOST (bulk-driven MOS transistor) technique operating in a subthreshold region is used. The proposed CDTA is designed in 0.18 µm CMOS technology, can operate with a supply voltage of 0.5 V, and consumes 1.05 μW of power. The proposed CDTA is used to realize a current-mode universal filter. The filter can realize five standard transfer functions of low-pass, band-pass, high-pass and band-stop, and all-pass from the same circuit. Neither component-matching conditions nor input signals of the inverse type are required to realize these filter functions. The current-mode filter offers low-input and high-output impedance and uses grounded capacitors. The natural frequency and quality factor of the filters can be orthogonally controlled. The proposed CDTA and its applications are simulated using SPICE to confirm the feasibility and functionality of the new circuits.